Hello World : For the Post-Human Age. - Yamamine, Junya; Goto, Oko (Ibaraki : Contemporary Art Center, Art Tower Mito, 2018)
Evans, Cécile B. ; Cobayashi, Kenta ; exonemo ; Blandy, David ; Steyerl, Hito ; Taniguchi, Akihiko ; Denny, Simon ; Maclean, Rachel
Hello Worls - For the Post-Human Age, Contemporary Art Gallery, Art Tower Mito, Ibakari, February 10 - May 6, 2018
boek